Block Center Learning of Sekolah Penggerak: Portrait of Merdeka Belajar in Kindergarten - Wildan Saugi; Mirsa Damayun; Lina Revilla Malik (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Block center learning in kindergarten is influenced by government education programs, including the driving school program as a school that pioneered the implementation of the independent curriculum. This study aims to analyze the implementation of block-center learning integrated with the driving school program. This research is field research with a qualitative approach. The research subjects were school principals, teachers, and students of driving schools. Data was collected through interviews, observation, and documentation techniques, which were then analyzed through condensation, data presentation, and conclusion. The study results show that block center learning implementation consists of planning by designing teaching modules and lesson plans, determining methods and media, and developing themes, sub-themes, and topics. Second, implementation is carried out on four bases according to the BCCT learning model guidelines. Several adjustments support forming a Pancasila student profile and reflect independent learning. Child development evaluation is carried out through an assessment using a work record instrument. This study concludes that government support, facilities and infrastructure, various online platforms, the readiness of educators and education staff, and simplification of curriculum instruments are very important to support the successful implementation of learning. Inhibiting factors in the implementation of learning must be mitigated by various policies at the school level and from the government so that learning can run better.